Cross-sectional study of correlation between mandibular incisor crowding and third molars in young Brazilians - Karasawa, Lilian H. (Medicina Oral S.L., 2013)
Objectives: The aim of this study was to evaluate transversally the clinical correlation between lower incisor crowding and mandible third molar. Study Design: Three hundred healthy volunteers (134 male and 166 female), aged 20.4 (±2.4) years-old were submitted to a complete clinical examination and filled up a questionnaire about gender, age, total teeth number and presence or absence of superior and inferior third molar. After a recent panoramic radiography were evaluated. The multiple logistic regression showed that none of the studied factors influenced the mandibular incisor crowding. Results: The proportion of both molars present or both absent was higher than the other conditions (Chi-square, p<.0001). The multiple logistic regression showed that any of the studied factors, influenced (p>.05) the mandibular incisor crowding. Despite the statistical significance, wear orthodontics appliances showed a little correlation (odds ratios < 1.0) in the mandibular incisor crowding. Conclusion: Presence of maxillary and/or mandibular third molars has no relation with the lower incisor crowding. Key words:Malocclusion, third molars, lower incisor crowding, mandible.